2013
DOI: 10.1042/bsr20120065
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, cellular uptake and angiogenic suppression of shikonin-containing liposomes in vitro and in vivo

Abstract: Shikonin has anticancer activity, but it has not yet been applied into clinical use. In the present study, shikonin was prepared using liposomes. We aimed to examine several aspects of sh-L (shikonin-containing liposomes): preparation, angiogenic suppression and cellular uptake through self-fluorescence. Sh-L were prepared using soybean phospholipid and cholesterol to form the membrane and shikonin was encapsulated into the phospholipid membrane. Three liposomes were prepared with shikonin. They had red fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
4

Year Published

2013
2013
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 25 publications
1
13
0
4
Order By: Relevance
“…One shikonin molecule binds covalently to β-lactoglobulin via Cys121, whereas the remaining pigment molecules most probably bind to the protein via non-covalent interactions. In order to facilitate cellular intake, Xia et al [7] prepared shikonin-containing liposomes using shikonin, soybean phospholipid and cholesterol, and dehydrated alcohol. The lipo- somes were used to study the angiogenic suppression and cellular uptake by the MTT assay, Transwell tests, as well as chick chorioallantoic membrane and Matrigel plug assays, which demonstrated that shikonin liposomes decreased toxicity, rate of inhibition of migration, and angiogenic suppression compared to free shikonin.…”
Section: The Pharmacokinetics and Bioavailability Of Shikoninmentioning
confidence: 99%
“…One shikonin molecule binds covalently to β-lactoglobulin via Cys121, whereas the remaining pigment molecules most probably bind to the protein via non-covalent interactions. In order to facilitate cellular intake, Xia et al [7] prepared shikonin-containing liposomes using shikonin, soybean phospholipid and cholesterol, and dehydrated alcohol. The lipo- somes were used to study the angiogenic suppression and cellular uptake by the MTT assay, Transwell tests, as well as chick chorioallantoic membrane and Matrigel plug assays, which demonstrated that shikonin liposomes decreased toxicity, rate of inhibition of migration, and angiogenic suppression compared to free shikonin.…”
Section: The Pharmacokinetics and Bioavailability Of Shikoninmentioning
confidence: 99%
“…A number of the agents have been shown to have low bioavailability (quercetin, curcumin, shikonin), and others have been suggested that oral administration may not be sufficient for therapeutic levels to be reached or indeed maintained [ 149 ]. Further, those that have low bioavailability which are then either manipulated or other proteins added this structural alteration may affect both adverse events and the actual therapeutic mechanisms [ 150 , 151 ]. To date, there remains a paucity of information in regard to the safety of some of these agents in their use as anti-scarring products.…”
Section: Reviewmentioning
confidence: 99%
“…The incorporation of a hydrophobic drug (such as shikonin) into liposomes improves its bioavailability and leads to increased stability and anticancer activity, along with decreased drug toxicity. Regarding shikonin, it has been recently proven that liposomes significantly decrease its toxicity in vitro and in vivo [27]. Furthermore, under the frame of developing drug delivery systems with alkannins and shikonins as bioactive molecules, we have successfully incorporated shikonin into both conventional (with lipids such as egg phosphatidylcholine (EPC), 1,2-dipalmitoylphosphatidylcholine (DPPC) and 1,2-distearoyl-sn-glycero-3-phosphocholine (DSPC)) [28] and stealth liposomes (DSPC-PEG 2000 , EPC-PEG 2000 , DPPC-PEG 2000 ) [29].…”
Section: Introductionmentioning
confidence: 99%